2021
DOI: 10.1016/j.scitotenv.2021.146749
|View full text |Cite
|
Sign up to set email alerts
|

Implementing building-level SARS-CoV-2 wastewater surveillance on a university campus

Abstract: The COVID-19 pandemic has been a source of ongoing challenges and presents an increased risk of illness in group environments, including jails, long-term care facilities, schools, and residential college campuses. Early reports that the SARS-CoV-2 virus was detectable in wastewater in advance of confirmed cases sparked widespread interest in wastewater-based epidemiology (WBE) as a tool for mitigation of COVID-19 outbreaks. One hypothesis was that wastewater surveillance might provide a cost-effective alternat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(161 citation statements)
references
References 27 publications
4
155
1
1
Order By: Relevance
“…Consideration of the challenges of each sampling approach is critical for developing effective wastewater monitoring programs, which could become increasingly more relevant as vaccination programs begin to take shape globally. 21,22 A passive sampling approach provides a cost effective and relatively easy option to grab and composite sampling. This approach involves the use of a passive sampling device which is deployed at a location in the sewershed for a predetermined period, and contaminants in the wastewater are allowed to interact with an adsorbent material housed inside the device, 23,24 which results in the concentration of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the challenges of each sampling approach is critical for developing effective wastewater monitoring programs, which could become increasingly more relevant as vaccination programs begin to take shape globally. 21,22 A passive sampling approach provides a cost effective and relatively easy option to grab and composite sampling. This approach involves the use of a passive sampling device which is deployed at a location in the sewershed for a predetermined period, and contaminants in the wastewater are allowed to interact with an adsorbent material housed inside the device, 23,24 which results in the concentration of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such challenges, many respondents remained positive about the potential for wastewater surveillance to enhance colleges’ pandemic responses. Several colleges have produced case study articles about their experiences that highlight the effectiveness of wastewater surveillance as part of a larger strategy for controlling COVID-19 transmission on campus, and particularly about the opportunity for identifying people with asymptomatic infections [ 2 , 50 , 51 ]. Although comparison to the counterfactual is not possible (i.e., we cannot know whether case rates would have differed without wastewater monitoring), many respondents reported that they believed it was helpful.…”
Section: Resultsmentioning
confidence: 99%
“…Measures like mandatory vaccination for students, faculty and staff, 17 testing of sewage for antigen to SARS-CoV-2, 18 and regular testing of the entire population 19 are more likely to be effective. While many students have antibodies due to previous infection, it is not clear how durable that immunity is.…”
Section: Discussionmentioning
confidence: 99%